CYTOGENETIC FINDINGS IN ACUTE MYELOID LEUKEMIA - Gh. Toogeh; A. H. Najafi M. Keyhani (Acta Medica Iranica, 2003)
Cytogenetics has now been well established as one of the most valuable prognostic factors in acute myeloid leukemia (AML). This is the first study to describe the cytogenetic findings in Iranian AML patients. During 1998 to 2001, 104 patients with adult de novo AML (excluding M3) were diagnosed and treated with the standard protocols in our center. Adequate cytogenetic analysis performed on bone marrow at diagnosis was available in 39 of these patients. Clonal chromosomal abnormalities were detected in 74.4% of the patients. The chromosomal changes seen in this study in order of frequency were: t(9;22), trisomy 11 [n=4, 10.3%], trisomy 8, Abn (3q)[n=3, 7.7%], trisomy 22, monosomy 7/del (7q), monosomy X, complex karyotype [n=2, 5.1%], and t (8;21), t (6;9), trisomy 21, monosomy 5/del (5q), monosomy Y, and Abn (11q) [n=1, 2.6%]. We also categorized the patients into favorable (2.6%), intermediate (74.4%), and unfavorable (23.1%) prognostic groups based on the criteria defined by Grimwade et al in MRC-AML-10. The frequencies of different clinical and paraclinical indices were studied in these groups. Notably, complete remission (CR) rates after one cycle of chemotherapy were 60.0% and 25.0% in intermediate and unfavorable prognostic groups respectively. The overall CR rates were 83.3% and 66.6% in the mentioned groups. These findings are somewhat comparable to the results of the larger studies in other countries, suggesting the importance of cytogenetics in Iranian patients. The differences could be due to methodological variations (notably exclusion of AML-M3 in this study), and the small sample size, although ethnic and geographical differences should not be disregarded. To further clarify these results with statistical significance a larger analytical study with a greater sample size is certainly needed